Multiple odontogenic keratocysts in Ehlers-Danlos syndrome: a rare case report - Anna Starzyńska; Paulina Adamska; Łukasz Adamski; Aleksandra Sejda; Piotr Wychowański; Michał Studniarek; Barbara Alicja Jereczek-Fossa (BMC, 2021)
Abstract Background An odontogenic keratocyst is a lesion characterized by aggressive and infiltrative growth. The lesion is characterized by the existence of satellite microcysts (microtumours) and frequent recurrence (up to 30%). Ehlers-Danlos syndrome is a condition in which collagen production or its post-translational modifications are affected. Defects in connective tissues cause symptoms, which range from mild joint hypermobility to life-threatening complications. Case presentation We present an extremely rare case of an 11-year old girl with Ehlers-Danlos syndrome and coexistence of multiple odontogenic keratocysts. Conclusions This case shows mainly atypical or rare association between multiple odontogenic keratocysts and Ehlers-Danlos syndrome.